2016
DOI: 10.1088/0965-0393/24/4/045017
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic properties of average-atom interatomic potentials for alloys

Abstract: The atomistic mechanisms of deformation in multicomponent random alloys are challenging to model because of their extensive structural and compositional disorder. For embedded-atom-method interatomic potentials, a formal averaging procedure can generate an average-atom EAM potential and this average-atom potential has recently been shown to accurately predict many zero-temperature properties of the true random alloy. Here, the finite-temperature thermodynamic properties of the average-atom potential are invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Recent work employing thermodynamic integration along alchemical mutation of random alloys into average-atom solids [73] have shown that free-energy differences between the true random alloy and the average-atom solid are on the order of ∼ 10 meV at 300 K. We expect that similar corrections apply for the energy differences computed in this work. All energies obtained here with the average-atom potential method are at least an order of magnitude larger than this energy scale.…”
Section: Appendix a Alloy-averaged Interatomic Potentialssupporting
confidence: 67%
“…Recent work employing thermodynamic integration along alchemical mutation of random alloys into average-atom solids [73] have shown that free-energy differences between the true random alloy and the average-atom solid are on the order of ∼ 10 meV at 300 K. We expect that similar corrections apply for the energy differences computed in this work. All energies obtained here with the average-atom potential method are at least an order of magnitude larger than this energy scale.…”
Section: Appendix a Alloy-averaged Interatomic Potentialssupporting
confidence: 67%
“…We attribute this effect to the asymmetry of the interatomic interaction potential, which makes close-packed AuAu pairs less affected by the presence of Pd atoms. Such information will be useful for future developments of interatomic potential models for alloys, which is a challenging task. , …”
Section: Exafs Modeling In Multielement Materialsmentioning
confidence: 99%
“…Under these conditions, the EAM functions of the A-atom are simply the concentration-weighted averages of the pure element functions. The accuracy of the A-atom method has been demonstrated for a wide range of properties [79] and at finite temperatures [81].…”
Section: Average Alloysmentioning
confidence: 99%